INFOMASI ORGANISASI HUMAS RUMAH SAKIT PUSAT PERTAMINA (RSPP) JAKARTA DALAM PENANGANAN KELUHAN - Deni Haryadi (2022)
This study discusses how the Public Relations (Customer Retention Management) of Pertamina Jakarta Central Hospital in handling complaints / com4plaints. This study aims to find out how Organizational Information is carried out by Public Relations (Customer Retention Management) in handling complaints. This research uses qualitative methods. The theory used is Organizational Information. Key Informants and informants are selected purposively. Data was collected through interviews with Senior Officer Customer Retention Management, Chief Business Manager, Doctor and Customer. The results of the research that has been carried out are information on the Public Relations (Customer Retention Management) organization in handling complaints, namely by collaborating with each rank of the Hospital. These efforts can maintain the good name of the Hospital which shows that Public Relations (Customer Retention Management) has a very important role in establishing good relations with the public